Peace at the Lily. The De Franceschi section in the stockbook of Bernardino Giunti - Flavia Bruni (JLIS.it, 2018)
This contribution investigates the catalogue of publications by Francesco De Franceschi, printer, publisher and bookseller between 1561 and 1599, and his heirs, who took over his business until 1624, as recorded in the stockbook of Bernardino Giunti (Los Angeles, University of California Library, Department of Special Collections, call number 170/622), also a printer, publisher and bookseller in Venice at the beginning of the seventeenth century. Each entry of this De Franceschi section has been matched with the edition it was meant to describe, in order to analyse the price of each book according to the Giunti stockbook as the result of material features and book marketing strategies.